Effect Of Different Nutrient Medium On Growth Of Lemna Gibba During In Vitro Culture - PATEL HARIKRUSHNA; SUTHAR RAMCHANDRA; DR. P. K. PATEL (International Journal of Pharma and Bio Sciences, 2015)
Duckweed as Lemna spp. have been used in various types of research. The effects of Murashige and Skoog (MS), B5 (Gamborg) and White media on survival growth rate of lemna gibba during in vitro cultivation and the effect on different concentrations of media were investigated. Under in vitro conditions, frond proliferation of Lemna gibba in white medium were 90% respectively faster than that in MS medium and B5 medium. Biomass production in White medium also increases compared to MS medium and B5 medium. The roots of lemna gibba in 1/16 MS medium and 1/16 B5 are distinctly shorter than 1/16 white medium. Root elongation of the frond colonies in MS, B5 and White media is comparable. The distinct effects of MS, B5 and White media on vegetative growth and survival growth rate is higher 70-90% in all concentrations of White media respected to MS and B5. White media with 1/16 concentrations of nutrients contain 1.25% sucrose as carbon source and six additional nutrients (Na2SO4, KCl, Ca(NO3)2.4H2O, Fe2(SO4)3, Ca-Pantothenate, Cysteine HCl), which were important for vegetative growth.